(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Erif, LOM, Djohan TS, Sudarmadji, Yasin A, Sudia LB, Kahirun. 2023. The application of the River Continuum Concept (RCC) on the headwaters of the Sampolawa River in Southeast Sulawesi, Indonesia. Biodiversitas 24: 290-299. Benthic aquatic insect communities in temperate regions have been used as bioindicators of a healthy forest in the stream headwaters.This research analyzes the abundance of benthic insects, the quality of water and nutrient sediment, and the response of the insect community in the Sampolawa River. The samples were collected using stratified random sampling methods with a Surber sampler 30 cm x 30 cm, 5 segmented streams, and 200 m with 4 replication. The results show that 19 species of 5 community feeding groups were found, including collector filters, gatherers, predators, scrapers, and shredders. However, the shredders community is very small, at about 2-4 %. The benthic insect aquatic dominance by collector filter with 29 % reflected that input from terrestrial vegetation is Fine Particulate Organic Matter (FPOM). Therefore, it can be deduced that Sampolawa headwaters do not fit with the prediction of the "River Continuum Concept (RCC)"for a typical headwater since the allochthonous energy supply from riparian vegetation is in the form of fine detritus.